Analisis Docking Molekuler terhadap Ligan Potensial pada Protein 7Q5F - Frisca Salda Putri; Ali Amran (MASALIQ, 2026)
The main protein of SARS-CoV-2 with PDB ID 7Q5F is one of the important targets in the development of antiviral drug candidates. This study aims to evaluate the potential of natural compounds from gambir (Uncaria gambir) in inhibiting the activity of the 7Q5F protein through the molecular docking method. The protein and ligand structures were prepared using MOE 2022 software, followed by docking simulations to analyze the strength and stability of the interactions based on binding energy (S-score) and RMSD values. The results showed that linalool had better interaction ability, with an S-score of -4.48 and an RMSD of 0.79 Å, compared with limonene, which had an S-score of -4.04 and an RMSD of 3.13 Å. These findings indicate that linalool is more stable and more precise in binding to the active site of the 7Q5F protein. Thus, natural compounds from gambir, particularly linalool, have the potential to be developed as antiviral drug candidates against SARS-CoV-2. This study provides an initial contribution to the exploration of plant-based compounds as antiviral therapeutic candidates, although further validation through laboratory research is still required.